It Is Time for a Routine Measurement of Aortic Stiffness in Inflammatory Bowel Disease - Zanoli, Luca; Lentini, Paolo; Gaudio, Agostino; Castellino, Pietro (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Zanoli L, Lentini P, Gaudio A, Castellino P. It is time for a routine measurement of aortic stiffness in inflammatory bowel disease. Turk J Gastroenterol. 2022;33(6):539-540.